The Hisab-Rukyat Method and Religious Tolerance: A Social Interpretation of Pancasila Values - Hamas, Nuril Fathoni; Andri, Sela Septi; Izzuddin, Ahmad (Pancasila: Jurnal Keindonesiaan, 2025)
Differences in determining the beginning of Qamariyah months-especially Ramadan, Shawwal, and Dhu al-Hijjah-often lead to socio-religious dynamics in Indonesia. This phenomenon reflects the tension between hisab (astronomical calculation) and rukyat (direct observation), each rooted in distinct theological and epistemological traditions within Islam. This paper aims to explore how the differences between the hisab and rukyat methods can be socially interpreted as a reflection of religious tolerance in the framework of Pancasila ideology. The study employs a qualitative approach using library research and social interpretation analysis of normative texts and social practices. The findings indicate that variations in determining the start of the lunar month should not be seen as a source of conflict but rather as a space for dialogue and respect for religious diversity. Within the context of Pancasila-particularly the third and fifth principles-tolerance toward differing religious interpretations serves as a crucial foundation for social harmony and national integration. Thus, the hisab-rukyat methods possess not only astronomical and religious dimensions but also socio-political values that support cohesion in a pluralistic society.